The dung beetle assemblage and their relationship with the mammals and the phytophysiognomies at Reserva Natural Vale, ES, Brazil - Couto, Fabiana Cassar de Barros (2018)
Dund Beetles (Scarabaeidae) are a group of insects, globally distributed with greatest diversity at the Tropics and Savannahs, probably because of their habit of feeding on mammalian dung, although they also feed on carcasses, decaing fruits and fungi. They play several roles in the ecosystem, which include nutrient cycling, bioturbation, plant growth enhancement, secondary seed dispersal, parasite suppression, enteric parasite reduction, fly control, trophic regulation and pollination. Due to these functions they have become an excellent source of environmental quality and are susceptible directly and indirectly to disturbances on the environment and on the mammals assemblages. In places where hunting pressure is strong and mammals begin to die out, beetles can be affected in their abundance, richness and community composition through a cascading effect. Dung beetles assemblages in tropical forests also depend habitat characteristics such as vegetation structure, diverging between primarian tropical forests, secondary forests and plantations. Vale Natural Reserve(RNV) along with Sooretama Biological Reserve, form a continuous block of vegetation native to the lowland, where there is a mosaic of phytophysiognomies, sheltering a rich fauna of medium and large mammals, some of them threatened of extinction and other endemic. Anthropogenic pressure in these areas is very strong on mammals due to illegal hunting and the presence of roads and highways. In this context, the purpose of this study was to get to know the dung beetles assembly in the Vale Natural Reserve(RNV) and its relationship with the assembly of medium and large mammals and the different phytophysiognomies. The study was developed from April to September 2016 in 21 plots of 250m of extension. In each plot six pitfall traps for dung beetles and a camera trap were established. Vegetation structure measurements were taken at 25 points in the plot. We reduced the composition and abundance of dung beetles through NMDS and related through multiple regression with vegetation structure and mammals biomass. We collected 13708 individuals of dung beetles belonging to 32 species, four of them had never been recorded at the area previously and one species is an exotic invasive. We recorded 23 species of medium and large mammals at the area, the total biomass in each plot ranged from 2341 to 10723kg. The results of the multiple regressions showed that the dung beetles assembly is strongly related to the vegetation structure when we compared plots in open and closed phytophysiognomies. However, the dung beetles assembly responds to mammalian biomass when we analyze only the plots located in forest areas. Our results corroborate the hypothesis that te assemblage of dung beetles is structured by mammals biomass and vegetation structure. Future analyzes are needed to improve our understanding of whether there is any specificity certain mammalian species dung and dung beetles species